Almonertinib plus chemotherapy versus almonertinib alone in second-line treatment of advanced non-small cell lung cancer with mutated epidermal growth factor receptor: a retrospective study - Fang, Xiaoxu; Xiang, Yan; Lu, Kaihua (Frontiers in Oncology, 2023)
Objective This study mainly observes the efficacy and safety of almonertinib plus chemotherapy compared with almonertinib alone in the second-line treatment of advanced non-small cell lung cancer (NSCLC) with mutated epidermal growth factor receptor (EGFR). Methods In this study, clinical data of 68 patients with advanced NSCLC who were treated in Jiangsu Provincial People’s Hospital and Nanjing Chest Hospital between April 2020 and December 2022 were collected. Among them, the study group (n=30) received second-line almonertinib combined with platinum-based chemotherapy, while the control group (n=38) received almonertinib alone. The near-term and long-term effects and adverse events of the two groups were compared respectively. Results The median follow-up time until 31 December 2022 was 16.3 months (95% CI: 11.32-21.34). Results of chi-square analysis showed no statistically significant difference in objective response rate (ORR) and disease control rate (DCR) between the study group and the control group (56.73% vs. 55.3%, P>0.05; 100% vs. 86.8%, P>0.05). Log-rank test comparing the two groups revealed that the median progression-free survival (mPFS) of the study group was significantly longer than that of the control group by 3.1 months (12.7 vs. 9.6 months, P=0.01). Multivariate COX proportional risk model showed a statistically significant effect of treatment method and PS score on PFS (HR=0.43, P=0.023; HR=3.82, P=0.001). In terms of safety, most of the adverse events (AEs) were mild, with no grade 4-5 in the two groups, and the overall tolerance of patients was good. Conclusion For advanced NSCLC patients with EGFR mutations, second-line treatment with almonertinib plus chemotherapy significantly improved PFS compared with almonertinib alone without a significant increase in adverse events, providing efficacy and safety.